A COVID-19 isolation facility for people experiencing homelessness in Berlin, Germany: a retrospective patient record study - Merle Hörig; Sarah M. Klaes; Svetlana Krasovski-Nikiforovs; Welmoed van Loon; Lukas Murajda; Rosa C. O. Rodriguez; Christine Schade; Anabell Specht; Gabriela Equihua Martinez; Ruth Zimmermann; Frank P. Mockenhaupt; Joachim Seybold; et al. (Frontiers Media S.A., 2023)
IntroductionPeople experiencing homelessness (PEH) are disproportionately affected by the COVID-19 pandemic. For many PEH it is impossible to isolate due to the lack of permanent housing. Therefore, an isolation facility for SARS-CoV-2 positive PEH was opened in Berlin, Germany, in May 2020, offering medical care, opioid and alcohol substitution therapy and social services. This study aimed to assess the needs of the admitted patients and requirements of the facility.Materials and methodsThis was a retrospective patient record study carried out in the isolation facility for PEH in Berlin, from December 2020 to June 2021. We extracted demographic and clinical data including observed psychological distress from records of all PEH tested positive for SARS-CoV-2 by RT-PCR. Data on duration and completion of isolation and the use of the facilities' services were analyzed. The association of patients' characteristics with the completion of isolation was assessed by Student's t-test or Fisher's exact test.ResultsA total of 139 patients were included in the study (89% male, mean age 45 years, 41% with comorbidities, 41% non-German speakers). 81% of patients were symptomatic (median duration 5 days, range 1-26). The median length of stay at the facility was 14 days (range 2-41). Among the patients, 80% had non-COVID-19 related medical conditions, 46% required alcohol substitution and 17% opioid substitution therapy. Three patients were hospitalized due to low oxygen saturation. No deaths occurred. Psychological distress was observed in 20%, and social support services were used by 65% of PEH. The majority (82%) completed the required isolation period according to the health authority's order. We did not observe a statistically significant association between completion of the isolation period and sociodemographic characteristics.ConclusionThe specialized facility allowed PEH a high compliance with completion of the isolation period. Medical care, opioid and alcohol substitution, psychological care, language mediation and social support are essential components to address the specific needs of PEH. Besides contributing to infection prevention and control, isolation facilities may allow better access to medical care for SARS-CoV-2 infected PEH with possibly positive effects on the disease course.